Reindeer warble fly-associated human myiasis, Scandinavia - Kan B; Asbakk K; Fossen K; Nilssen A; Panadero R; OTRANTO, Domenico (Emerging Infectious Diseases, 2013)
We report migratory myiasis that occurred during 1991–2012 caused by the reindeer warble fly, Hypoderma tarandi (Technical Appendix Figures 1, 2), in 7 tourists to reindeer habitats of northern Scandinavia. We also report 2 additional women (patients 8 and 9), independent of each other, who were asymptomatic but sought medical care in August 2012 after finding 30–60 parasite eggs in scalp hair 3 days after hiking in Kebnekaise and Jämtland Mountains (northern Sweden), respectively.